Efficacy of viscous budesonide slurry for prevention of esophageal stricture formation after complete endoscopic mucosal resection of short-segment Barrett’s neoplasia - Bahin, Farzan F.; Jayanna, Mahesh; Williams, Stephen J.; Lee, Eric Y. T.; Bourke, Michael J. (Endoscopy, 2016)
Background and aims: Complete endoscopic resection (CER) of short-segment Barrett’s esophagus with high grade dysplasia (HGD) and early esophageal adenocarcinoma (EEA) is a precise staging tool and achieves durable disease control. The major drawback is development of post-endoscopic resection esophageal stricture (PERES). No effective therapy to prevent PERES has been described. Viscous budesonide slurry (VBS) may have a role in the prevention of PERES by suppressing the post-CER inflammatory process. The study aim was to evaluate the efficacy of VBS for the prevention of PERES.Methods: Prospective data were collected on patients referred for CER of HGD or EEA. After January 2012, patients routinely received VBS (two 0.5-mg/2-mL budesonide respules mixed with sucralose) twice daily for 6 weeks following each stage of the CER schedule. All patients received high dose proton pump inhibitor therapy for the duration of CER and the following 3 months. Patients had no other intervention to prevent PERES. A validated dysphagia score was used (0 – 4, no dysphagia to aphagia). Endoscopic dilation was performed for dysphagia. Patients receiving VBS were compared with historical controls. The primary endpoint was the need for dilation.Results: Between January 2008 and January 2015, 104 of 116 eligible patients completed CER. The VBS group (n = 29) and non-VBS group (n = 75) had similar patient, disease, and procedural characteristics. Dilations were needed in 13.8 % vs. 37.3 % (P = 0.03), with a median of one vs. two procedures (P = 0.01), and median dysphagia score during CER of 0 vs. 1 (P = 0.02) in the VBS and non-VBS groups, respectively. No VBS-related adverse events were noted. Conclusion: In this pilot study VBS significantly reduced PERES and shortened the dilation program after CER.